ANALISIS EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI (STUDI EMPIRIS PADA HOTEL-HOTEL BERBINTANG DI BANDA ACEH) - qashdina, qashdina; Evayani, Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this study is to determine the effectiveness of the accounting information system implementation that applied by star hotels in Banda Aceh. The population in this study were all hotels in Banda Aceh City totaling 61 hotels and samples were star hotels in Banda Aceh City that using accounting information system totaling 14 hotels. This research is a quantitative research. This study used questionnaire method which distributed to 42 respondents. Test instrument used is the test of validity and reliability test. The results show that the accounting information system applied by star hotels in Banda Aceh has been effective.